Feminism and International Relations. Conversations about the Past, Present and Future. - Busconi, Antonela (CUPEA Cuadernos de Política Exterior Argentina, 2020)
Reseña del libro: TICKNER, J. A.; SJOBERG, L. (Eds.) (2013). Feminism and International Relations. Conversations about the Past, Present and Future, 1st Edition, Routledge. 274 páginas.